Efficacy and safety of intravenous ferric carboxymaltose compared with oral iron for the treatment of iron deficiency anaemia in women after childbirth in Tanzania: a parallel-group, open-label, randomised controlled phase 3 trial. Issue 2 (February 2021) - Vanobberghen, Fiona; Lweno, Omar; Kuemmerle, Andrea; Mwebi, Kwaba Dennis; Asilia, Peter; Issa, Amina; Simon, Beatus; Mswata, Sarah; Schmidlin, Sandro; Glass, Tracy R; Abdulla, Salim; Daubenberger, Claudia; et al.
Summary: Background: Iron deficiency anaemia is of major concern in low-income settings, especially for women of childbearing age. Oral iron substitution efficacy is limited by poor compliance and iron depletion severity. We aimed to assess the efficacy and safety of intravenous ferric carboxymaltose versus oral iron substitution following childbirth in women with iron deficiency anaemia in Tanzania. Methods: This parallel-group, open-label, randomised controlled phase 3 trial was done at Bagamoyo District Hospital and Mwananyamala Hospital, Tanzania. Eligible participants were close to delivery and had iron deficiency anaemia defined as a haemoglobin concentration of less than 110 g/L and a ferritin concentration of less than 50 μg/L measured within 14 days before childbirth. Participants were randomly assigned 1:1 to receive intravenous ferric carboxymaltose or oral iron, stratified by haemoglobin concentration and site. Intravenous ferric carboxymaltose was administered at a dose determined by the haemoglobin concentration and bodyweight (bodyweight 35 kg to <70 kg and haemoglobin ≥100 g/L: 1000 mg in one dose; bodyweight 35 kg to <70 kg and haemoglobin <100 g/L, or bodyweight ≥70 kg and haemoglobin ≥100 g/L: 1500 mg in two doses at least 7 days apart; bodyweight ≥70 kg and haemoglobin <100 g/L: 2000 mg in two doses at least 7 days apart). Oral iron treatment consisted of three dried ferrous sulphate tablets of 200 mg containing 60 mg of elementary iron and 5 mg of folic acid every morning. Oral treatment was to be taken for 3 months after haemoglobin normalisation. The primary outcome was haemoglobin normalisation (>115 g/L) at 6 weeks. Follow-up visits were at 6 weeks, and 3, 6, and 12 months. Analyses were done in the modified intention-to-treat population of participants who had a 6-week haemoglobin concentration result, using logistic and linear regression models for binary and continuous outcomes, adjusted for baseline haemoglobin concentration and site. This trial is registered with ClinicalTrials.gov, NCT02541708 . Findings: Between Oct 8, 2015, and March 14, 2017, 533 individuals were screened and 230 were enrolled and randomly assigned to a study group (114 to intravenous iron, 116 to oral iron). At 6 weeks, 94 (82%) participants in the intravenous iron group and 92 (79%) in the oral iron group were assessed for the primary outcome. 75 (80%) participants in the intravenous iron group and 47 (51%) in the oral iron group had normalised haemoglobin (odds ratio 4·65, 95% CI 2·33–9·27). There were two mild to moderate infusion-related adverse events; and five serious adverse events (three in the intravenous iron group, two in the oral iron group), unrelated to the study medication. Interpretation: Intravenous iron substitution with ferric carboxymaltose was safe and yielded a better haemoglobin response than oral iron. To our knowledge, this is the first study to provide evidence of the benefits and safety of intravenous iron substitution in a low-income setting. Funding: Vifor Pharma, R Geigy-Stiftung, Freiwillige Akademische Gesellschaft, and Swiss Tropical and Public Health Institute.